2 MW Closed Cycle SWOTEC in Mentawai, Sumatera Barat, Indonesia - Koto, Jaswar (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2016)
Solar, Wind and Ocean Thermal Energy Conversion (SWOTEC) is a clean marine renewable energy using temperature difference between the sea surface and the deep ocean to rotate a generator to produce electrical energy. Indonesia is an equatorial country located at latitudes less than 20 degrees covered by 77 % ocean, thousand islands, strain and many difference of topography, SWOTEC is very compatible build in Indonesian. This paper discussed on performance of 2MW closed cycle of SWOTEC in Siberut Island, Sumatera Barat-Indonesia. Siberut Island has a hot and humid tropical rainforest climate, with an annual rainfall of 4,000 mm with temperatures range 22 - 31 0C and humidity averages 81-85%. The study founded that the Siberut island has potential SWOTEC due to the gradient temperature more than 20 0C. The electricity and fresh water generated by the SWOTEC are more promising to be applied in the island.